Health and safety : risk management - Boyle, Tony (Health and safety consultant); Charlton, Fiona (Routledge, 2024)
The sixth edition of this text on risk management and industrial safety takes into account new developments in legislation, standards, and good practice. ISO 45001, the international health and safety management system standard, is given comprehensive treatment together with the guidance in ISO 45002. The latest ISO 10013 has also been addressed. The book is divided into four main parts. Part 1.1 begins with a basic introduction to the techniques of health and safety risk management and continues with a description of ISO 45001. Part 1.2 covers basic human factors including how the sense organs work and the psychology of the individual. Part 2.1 deals with more advanced techniques of risk management including advanced incident investigation, audit and risk assessment, and Part 2.2 covers a range of advanced human factors topics, including human error and decision making. This authoritative treatment of health and safety risk management is aimed at both students working towards degrees, diplomas, and postgraduate or vocational qualifications, and experienced health and safety professionals who will find it useful as a reference. -- Adapted from publisher's description.
Keywords: Industrial safety -- Management.; Industrial hygiene -- Management.; elektronické knihy; electronic books